DIRECTIONS OF DEVELOPMENT OF THE ENTERPRISE IN AGRICULTURE - Qurbonov Alisher Boboqulovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: The article is based on the specifics of agriculture and the role of entrepreneurship in it. The opinions of scientists conducting research in the field of agricultural entrepreneurship were also studied and analyzed. Modern problems and prospects of agriculture of the Republic of Uzbekistan are presented. Suggestions and recommendations were made on the lack of specialists in the field of agriculture and the solution of existing problems in the field of entrepreneurship.